Thermal unfolding of the DNA-binding protein Sso7d from the hyperthermophile Sulfolobus solfataricus. - Knapp, S; Karshikoff, A; Berndt, K; Christova, P; Atanasov, B; Ladenstein, R (1996)
Thermal unfolding of the small hyperthermophilic DNA-binding protein Sso7d was studied by circular dichroism spectroscopy and differential scanning calorimetry. The unfolding transition can be described by a reversible two state process. Maximum stability was observed in the region between pH 4.5 and 7.0 where Sso7d unfolds with a melting temperature between 370.8 to 371.9 K and an unfolding enthalpy between 62.9 and 65.4 kcal/mol. The heat capacity differences between the native and the heat denatured states obtained by differential scanning calorimetry (620 cal/(molK)) and circular dichroism spectroscopy (580 cal/(mol K)) resulted in comparable values. The thermodynamic reason for the high melting temperature of Sso7d is the shallow stability curve with a broad free energy maximum, corresponding to the relatively small heat capacity change which was obtained. The calculated stability curve shows that Sso7d has, despite of its high melting temperature, an only moderate intrinsic stability, which reaches its maximum (approximately 7 kcal/mol) at 282 K. Sso7d is particularly poorly stabilized (approximately 1 kcal/mol) at the maximum physiological growth temperature of Sulfolobus solfataricus. Sso7d has furthermore untypically low specific enthalpy (0.99 kcal/(mol residue)) and entropy (2.99 cal/(mol K)) values at convergence temperatures. No significant differences in thermal stability of the partially methylated Sso7d from Sulfolobus solfataricus and the cloned non-methylated form of the protein expressed in Escherichia coli were observed.